Adventures in translating terms of sample survey theory and practice in social investigations and the non-existent «statistical error»: An annotated English-Greek glossary - Μιχαλοπούλου, Καίτη (The Greek Review of Social Research, 2012)
The paper presents an annotated English-Greek glossary of terms in sample survey theory and practice in social investigations, based mainly on the translation of statistical terms by Professors Athanasiadis, Kokolakis and Chryssafinou, the Greek Statistical Institute, the International Statistical Institute, and by the National Statistical Service of Greece in the documentation of its surveys. The findings show that sample survey theory and practice terms have been translated correctly by the National Statistical Service of Greece, while there is disagreement among statisticians even on basic statistical terms and «statistical error», a Greek invention, is non-existent as a statistical term.